Solitonic Solutions and Particle Localization in Higher Dimensional Spaces - Erman, Fatih; Erman, Fatih; Erdem, Recai (Izmir Institute of Technology, 2003)
First the basic extra dimensional theory (i.e. Kaluza-Klein theory) and the main aspects of solitons are reviewed. Then the current status of extra dimen-sional models and the application of solitons (especially kinks) in this context are studied. The extra dimensional models for fermion localization are considered with a particular emphasis. Finally a variation of these models which tries to in-corporate the best aspects of various models for fermion localization is presented.
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2003
Includes bibliographical references (leaves: 82-87)
Text in English; Abstract: Turkish and English
vii, 87 leaves
Keywords: QC174.26.W28 E76 2003; Solitons; Kaluza-Klein theories; Field theory(Physics); Fermions